Fueling Growth: Integrating Entrepreneurship Education into Medan’s Small Business Sector - Darwis Tamba; Peran Simanihuruk; Riko Fridolend Sianturi (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Entrepreneurship acts as a critical catalyst for mitigating structural unemployment and fostering economic resilience in developing nations such as Indonesia. Despite its strategic importance, the translation of psychological readiness into tangible business action remains a persistent challenge within the Micro, Small, and Medium Enterprise (MSME) sector. This study investigates the structural pathways of the Theory of Planned Behavior (TPB) to determine how cognitive antecedents drive actual entrepreneurial behavior, focusing specifically on the intervening role of entrepreneurship education. Data were collected from a purposive sample of 248 MSME practitioners in Medan, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results reveal an asymmetrical structural mechanism that challenges conventional TPB assumptions. Specifically, Attitude toward the Behavior and Subjective Norms exert powerful, direct impacts on entrepreneurial execution, operating independently of educational interventions. In stark contrast, Perceived Behavioral Control (PBC) fails to influence behavior directly; rather, its structural utility is fully realized only when mediated by entrepreneurship education. These findings indicate that while intrinsic motivation and social expectations autonomously drive venture creation, perceived operational capacity requires the structural scaffolding of formal education to materialize into actual business practices. Consequently, this study provides a strategic blueprint for policymakers, demonstrating that MSME empowerment programs must pivot from purely motivational seminars toward practical, capability-building interventions that operationalize perceived control.